Grounded Coplanar Waveguide-fed Compact MIMO Antenna for Wireless Portable Applications - Taghizadeh, Hamed; Ghobadi, Changiz; Azarm, Burhan; Majidzadeh, Maryam (Společnost pro radioelektronické inženýrství, 2019)
A multi-input multi-output (MIMO) antenna with high isolation capability is proposed in this paper. The proposed MIMO antenna configuration is composed of two monopole antennas, each of them consists of a single rectangular grounded coplanar waveguide (GCPW) feed line, a radiation patch with two arms, two conductive elements on both sides of the feed line, and a simple ground plane on substrate backside. The overall size of the proposed MIMO antenna is 44×20 mm2 on 1.6 mm thick FR4 substrate which is more compact than many of the previously designed structures. The arrangement of two monopole antennas in the form of a MIMO antenna topology yield a dual-band operation in which the first bandwidth is in 3.06-3.89 GHz with the central frequency at 3.5 GHz for WiMAX applications, and 5.14-5.93 GHz with central frequency of 5.5 GHz for WLAN applications. Interestingly the obtained isolation level is better than -20 dB over the operating bandwithds. Simulation and measured results confirm the antenna outperformance in WiMAX and WLAN frequency range in wireless portable applications. Small size, simple structure, and high isolation without any decoupling elements are some of the advantages of the proposed design.
Keywords: Monopole antennas; multiple-input–multiple-output (MIMO); WiMAX applications; WLAN application; wireless portable devices